Association of GAB2 with Quality of Life and Negative Emotions in Patients with Gastric Cancer after Postoperative Comprehensive Care. (31st July 2022) - Zhuang, Juping; Yu, Jiejie; Yang, Yanchu
Abstract : GRB2-associated binding protein 2 (GAB2), a highly conserved scaffold protein, is abnormally expressed and activated in patients with gastric cancer (GC). However, the genetic diversity of GAB2 in GC and its association with the clinical manifestations of patients are still unclear. Here, we explored the polymorphism of GAB2 rs2373115 in GC and its association with quality of life (QOL) and negative emotions of patients with GC after postoperative comprehensive care. A case-control study showed that the frequency of the GG genotype of GAB2 rs2373115 in the GC patients was higher than that in the healthy people, while the frequency of the TT + TG genotype was lower than that in the healthy people. Obvious distinctions were observed in the histological grade and TNM staging between the GG genotype and TT + TG genotype. In addition, SAS and SDS scores in the patients with GG genotype were higher than those in patients with TT + TG genotype, while the emotional function, cognitive function, dyspnea, fatigue, sleep disorder, and overall QOL in patients with GG genotype were lower than those in patients with TT + TG genotype. These results showed that GAB2 rs2373115 polymorphism was related to QOL and negative emotions in patients with GC after postoperative comprehensive care.